An investigation of NIS expression in gastric tissue of obese individuals - Mihcioglu, Deniz; Ozbas Gerceker, Filiz; Aksoy, Basar; Yilmaz, Nimet; Hekim, Suleyman Nezih (Cellular and Molecular Biology, 2018)
Obesity is seen as one of the top ten (10) illness's listed by World Health Organization (WHO). It is a global problem that can affect people of all ages. Obesity is identified one of the most important factors leading to diabetes, heart disease and hypertension. Individuals with a Body Mass Index (BMI) above 40 kg/m2 are defined with morbid obesity. Sodium Iodide Symporter (NIS) gene is a plasma membrane glycoprotein that mediates iodide uptake in thyroid glands, stomach, salivary glands, lactating mammary glands and intestine. NIS gene transports iodide from the blood to the gastric epithelial cells. NIS gene expression and regulatory role of NIS gene in gastrointestinal tract, hasn't been studied yet in the individuals with obesity (i.e., BMI >40 kg/m2). In this study, gastric tissues were obtained by laparoscopic sleeve gastrectomy from 33 individuals diagnosed with obesity. Control group consisted of gastric tissue of 21 subjects with normal BMI obtained by endoscopy. RNA isolation, cDNA synthesis and qRT-PCR analyses were performed on the samples to determine NIS gene expression. Expression levels of NIS gene were compared between obese and control individuals, although an increase was observed in obese patients this difference was not found to be statistically important (p>0.05).